A multilevel strategy for the exploration of the conformational flexibility of small molecules - Forti, Flavio (2012)
Predicting the conformational preferences of flexible compounds is still a challenging problem with important implications in areas such as molecular recognition and drug design. In this work, we describe a multilevel strategy to explore the conformational preferences of molecules. The method relies on the predominant-state approximation, which partitions the conformational space into distinct conformational wells. Moreover, it combines low-level (LL) methods for sampling the conformational minima and high-level (HL) techniques for calibrating their relative stability. In the implementation used in this study, the LL sampling is performed with the semiempirical RM1 Hamiltonian, and solvent effects are included using the RM1 version of the MST continuum solvation model. The HL refinement of the conformational wells is performed by combining geometry optimizations of the minima at the B3LYP (gas phase) or MST-B3LYP (solution) level, followed by single point MP2 computations using Dunning's augmented basis sets. Then, the effective free energy of a conformational well is estimated by combining the MP2 energy, supplemented with the MST-B3LYP solvation free energy for a conformational search in solution, with the local curvature of the well sampled at the semiempirical level. Applications of this strategy involve the exploration of the conformational preferences of 1,2-dichloroethane and neutral histamine in both the gas phase and water solution. Finally, the multilevel strategy is used to estimate the reorganization cost required for selecting the bioactive conformation of HIV reverse transcriptase inhibitors, which is estimated to be at most 1.3 kcal/mol.